Warming effects on a nonindigenous predator are not conserved across seasons - Nora Theurich; Ross N. Cuthbert; Elizabeta Briski (Limnology and Oceanography, 2025)
The global proliferation of nonindigenous species remains a critical stressor driving both biodiversity loss and socioeconomic costs. These impacts frequently depend on environmental contexts, but few studies have investigated how seasonal variations coupled with climate changes, like warming, could modulate nonindigenous species ecological impacts. The Japanese brush‐clawed shore crab Hemigrapsus takanoi is a successful nonindigenous species in northern European waters and is currently spreading in the Baltic Sea. In this study, we used generalized linear models and the comparative functional response approach to examine the predatory impact of H. takanoi toward blue mussels Mytilus sp. across four seasons under current and future temperature scenarios (i.e., ambient and + 6°C warming). We further integrated H. takanoi Q 10 values and field abundances across seasons to examine population‐level feeding impacts toward blue mussels. The nonindigenous species exhibited a consistent type II functional response (i.e., inversely prey density‐dependent response) across all seasons, temperatures and sexes, with males consistently consuming more mussels than females across all seasons. Warming generally decreased handling times and increased attack rates, but these effects varied by season and sex, with the most pronounced temperature responses observed in autumn and spring. Population‐level impact calculations integrating field abundance data of H. takanoi indicated that under ambient conditions, feeding impacts toward blue mussels currently peak in the summer months, but as temperature increases, this feeding impact is anticipated to shift later in the year into autumn. These findings underline the critical need for multifaceted research approaches to better understand and predict the context‐dependent ecological impacts of nonindigenous species, particularly in the face of ongoing climate change and shifting population characteristics.